Gestão do turismo nas Serras Gerais – TO: uma análise da captação de recursos através do sistema de convênios do governo (SICONV) - Santos, Adno Ramalho dos (Universidade Federal do Tocantins, 2023)
This work has the objective of identifying how the fundraising for the management of tourism in the Sierras Gerais is carried out as of the SICONV. Methodological procedures were used for quantitative and qualitative research, exploratory, descriptive, documentary and field research with a semi-structured interview script. The results indicate that managers have faced several challenges in fundraising, in which the lack of knowledge of the SICONV tool for formatting projects and the bureaucracy found in the edicts made available by the Ministry of Tourism are highlighted. Increased funding could improve the infrastructure of the secretariats, have specialized professionals and develop public policies in the municipalities. It is concluded that the actions carried out by MTur are not satisfactory to meet the demands of tourism in the region of the Serras Gerais, on the other hand it was noticed that the secretariats are not prepared to take advantage of the opportunities offered by the Ministry of Tourism.